Sustainable operations management: A typological approach - Lawrence M. Corbett (Journal of Industrial Engineering and Management (JIEM), 2009)
This paper discusses the nature of sustainability and sustainable development as they relate to operations management. It proposes a typology for sustainable operations management that is based on the life cycle stages of a product and the three dimensions of corporate social responsibility. The aim is to show how this typology development could provide a useful approach to integrating the diverse strands of sustainability in operations, using industrial ecology and carbon neutrality as examples. It does this by providing a focused subset of environmental concerns for an industrial ecology approach, and some research propositions for the issue of carbon neutrality.
Keywords: 650; operations management; sustainability; environment; typology